Reaksi Pasar Modal terhadap Kunjungan Raja Arab dan Presiden Korea Selatan ke Indonesia - Laila Cahyaning Palupi; Ardian Prima Putra; Sari Widati (Universitas Veteran Bangun Nusantara, 2020)
The purpose of this study is to analyze the capital market reaction to a political event. The event of visitation of the Arab King to Indonesia on Maret 1st-9th 2017 and visitation of the President of South Korea to Indonesia on November 9th 2017 on the members of stock index LQ45. The sampling method used in this study was purposive sampling with a total sample of 30. The data analysis technique used was Paired Sample Test with the event period of 11 days. The results of the analysis show the following: 1) Not difference in average abnormal return before and after visitation of the Arab King to Indonesia. 2) There are difference in average trading volume activity before and after visit of the Arab King in Indonesia. 3) Not difference in average abnormal return and average trading volume activity before and after visitation of the President of South Korea to Indonesia. 4) The visitation of the Arab King to Indonesia has increased compared to the visitation of the President of South Korea to Indonesia.Keywords: event study; abnormal return; trading volume activity